Evaluasi Kebijakan Pengurangan Resiko Bencana di Kabupaten Pasaman - Ahmad, Taufani; Putera, Roni Ekha; Koeswara, Hendri (Journal of Civic Education, 2024)
The purpose of this study is to explain the evaluation of disaster management policies in the Pasaman regency. William N Dunn's criteria theory assessment is used in this qualitative descriptive study. The data-gathering methods used were observation, interviews, and documentation. The data analysis strategies are data reduction, data presentation, conclusions, and verification. The findings of this study shows that the objectives of Pasaman Regency's disaster risk reduction strategy have not been met and must be evaluated due to the suboptimal execution of disaster risk reduction activities. The effectiveness instrument revealed that actions, such as drafting contingency plans, had not been implemented, and the objectives of the disaster resistant village (Destana) and disaster awareness group (KSB) activities had not been met, resulting in this risk reduction policy not being enforced adequately. Next, a lack of human resources in terms of competence and funding has prevented various initiatives, such as the sustainability of Destana and KSB, from being implemented, failing to meet efficiency objectives. Next, the adequacy of Pasaman Regency's BPBD, such as the level of success of disaster risk reduction operations carried out, is deemed insufficient to address future issues. Then, it was discovered that the application of this policy did not create an even output in each Nagari that served as the study locus. In terms of the responsiveness of the implementation of the disaster risk reduction policy, which was carried out to elicit a positive response from the community, and finally, in terms of the accuracy of the implementation of this disaster risk reduction policy, it can be concluded that while it was right on target, it was not executed optimally.